RECONCEPTUALIZATION OF INDONESIA LAW SUBSTANCES - Rijadi, Prasetijo; Priyati, Sri (Faculty of Law, Universitas Brawijaya, 2017)
Law is designed to bring justice to the people and to establish good public order. The idea of rule of law construction encouraged fundamental changes to the rule of law itself in accordance with country's values and interests. This article focuses on what exactly the substance of law and examines how such substance is understood by society. Furthermore, it analyses the application of such substance of law within the society and government organization. It further intends to enable articulating and emphasizing the law and its actual application in